Research Progress of Fuel Mixing and Combustion Organization Technology in Air-Breathing Oblique Detonation Engine - Shang Jiahao, Cao Junwei (Hangkong bingqi)
The air-breathing oblique detonation engine (ODE) utilizing standing oblique detonation waves achieves stabilized combustion and highly efficient and rapid energy conversion in high Mach number flows. It holds significant potential and value as a propulsion system for hypersonic air-breathing applications. This paper reviews the recent advancements in the research of fuel mixing and combustion organization technology in ODE, including combustion chamber flow control, fuel sensitization, and fuel injection technologies. Additionally, it provides supplementary insights into the ground testing technology for ODE. Finally, based on the current status of fuel mixing and combustion organization technology and ground testing technology, this paper looks ahead to the future directions for technological development.